Effect of team sports and resistance training on physical function, quality of life, and motivation in older adults. (1st February 2017) - Pedersen, M. T.; Vorup, J.; Nistrup, A.; Wikman, J. M.; Alstrøm, J. M.; Melcher, P. S.; Pfister, G. U.; Bangsbo, J.
Abstract : The aim of this study was to investigate the effect of team sports and resistance training on physical function, psychological health, quality of life, and motivation in older untrained adults. Twenty‐five untrained men and forty‐seven untrained women aged 80 (range: 67‐93) years were recruited. Fifty‐one were assigned to a training group (TRG) of which twenty‐five performed team training (TG) and twenty‐six resistance training (RG). The remaining twenty‐one were allocated to a control group (CG). TRG trained for 1 hour twice a week for 12 weeks. Compared with CG, TRG improved the number of arm curls within 30 seconds ( P <.05) and 30‐seconds chair stand ( P <.05) during the intervention. In TRG, participation in training led to higher ( P <.05) scores in the subscales psychological well‐being, general quality of life, and health‐related quality of life, as well as decreased anxiety and depression levels. No differences between changes in TG and RG were found over the intervention period, neither in physical function tests nor psychological questionnaires. Both TG and RG were highly motivated for training, but TG expressed a higher degree of enjoyment and intrinsic motivation mainly due to social interaction during the activity, whereas RG was more motivated by extrinsic factors like health and fitness benefits. In conclusion, both team training and resistance training improved physical function, psychological well‐being, and quality of life. However, team sport training motivated the participants more by intrinsic factors than resistance training.